2019
DOI: 10.18203/2319-2003.ijbcp20190142
|View full text |Cite
|
Sign up to set email alerts
|

Drug utilization study of antihypertensive drugs and prevalence of blood pressure control in adult hypertensive patients based on JNC VIII guidelines in a tertiary care hospital: a cross sectional study

Abstract: Background: Hypertension is a major independent risk factor for coronary artery disease, congestive heart failure, stroke, chronic kidney disease and peripheral vascular diseases if left untreated. Drug utilization study of antihypertensive drugs and the study on prevalence of blood pressure control would help in reducing the burden of the disease and health expenditure.Methods: The study was conducted in the Outpatient Department of Medicine in Government Medical College, Thrissur. Patients aged 18yrs or abov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 11 publications
1
1
0
2
Order By: Relevance
“…Similar trend was observed in a study conducted in rural areas of Kerala by Ramadas et al that reported 4.19 as average number of drugs per prescription. 25 Maximum number of patients received multiple drug therapy (67.69%) which are comparable to findings in studies by Abegaz et al and Gupta et al that showed adequate management of HTN by utilising combination therapy. 20,26 It was observed that CCBs (19.23%) was the most commonly prescribed antihypertensive agent as monotherapy.…”
Section: Discussionsupporting
confidence: 85%
“…Similar trend was observed in a study conducted in rural areas of Kerala by Ramadas et al that reported 4.19 as average number of drugs per prescription. 25 Maximum number of patients received multiple drug therapy (67.69%) which are comparable to findings in studies by Abegaz et al and Gupta et al that showed adequate management of HTN by utilising combination therapy. 20,26 It was observed that CCBs (19.23%) was the most commonly prescribed antihypertensive agent as monotherapy.…”
Section: Discussionsupporting
confidence: 85%
“…This finding was also supported by a study by Raikar, Shrinivas R. et al 7 Average number of antihypertensive drugs per prescription in our study was 1.34 which were in favor of findings of other studies. According to Rimoy et al, 8 average number of antihypertensives was 1.6 whereas Ramada S. et al, 9 reported a similar number of average 1.4 antihypertensive drugs. The reason for a higher number of average drugs per prescription can be explained by the fact that most of the patients had associated comorbidity with hypertension.…”
Section: Discussion: Assessment Of Drug Utilization Of Antihypertensimentioning
confidence: 97%
“…Selain itu tujuan utama dari terapi hipertensi ini adalah mencapai serta mempertahankan target tekanan darah (Muhadi, 2016). Penurunan tekanan darah dengan modifikasi gaya hidup serta penggunaan obat antihipertensi dapat efektif dalam pengurangan penyakit ini (Ramadas et al, 2019). Pemilihan obat antihipertensi, dimana banyaknya obat antihipertensi yang semuanya efektif dalam menurunkan tekanan darah merupakan suatu yang sangat kompleks.…”
Section: Hubungan Antara Penyakit Penyerta Terhadap Keberhasilan Terapiunclassified
“…Tidak adanya kesadaran dan kurangnya kepatuhan juga menjadi faktor penyebabnya. Kebiasaan sosial seperti alkoholisme dan merokok bersamaan dengan tidak adanya atau ketidakcukupan intervensi gaya hidup seperti olahraga rutin setiap hari, penurunan berat badan, dan pembatasan garam juga dapat menghambat pengendalian tekanan darah (Ramadas et al, 2019).…”
Section: Hubungan Antara Penyakit Penyerta Terhadap Keberhasilan Terapiunclassified